Acompanhante terapêutico: caracterização da prática profissional na perspectiva da Análise do Comportamento - Marco, Mariana Nunes da Costa; Calais, Sandra Leal [UNESP] (My University, 2012)
Therapeutic Accompaniment as a clinical practice was born in the antipsychiatry political-ideological movement. Most research papers try to build a Therapeutic Accompaniment profile from the beginning of this historical context, but the concept has not yet reached a scientific consensus. Although there are some common characteristics, the Therapeutic Accompaniment’s diverse practice makes it difficult to identify the variables and consequently to built a final concept. The main purpose of this study was to characterize therapeutic companions under the behavior analysis perspective. Thirteen Therapeutic Companions, of both sexes, participated of this research. They were from the city of São Paulo and submitted to a semi-structured interview. The results were analyzed in four analysis dimensions and unfolded in categories. It is possible to observe that the Therapeutic Accompaniment’s profiles are constantly changing and to characterize them imply the observation of many variables that will be discussed here.

O Acompanhamento Terapêutico é uma atuação clínica nascida dos movimentos político-ideológicos da Antipsiquiatria. Boa parte da literatura tenta construir um perfil para o acompanhante terapêutico a partir do seu surgimento e contexto histórico. Entretanto, ainda não se chegou a um consenso científico, apesar de existirem alguns fatores característicos. A prática diversificada dificulta a identificação das variáveis e, consequentemente, a construção de um conceito definitivo. Com o objetivo de caracterizar o Acompanhamento Terapêutico sob a perspectiva da Análise do Comportamento, fez-se uso de descrições do trabalho desse profissional. Foram participantes treze acompanhantes terapêuticos, de ambos os sexos, atuantes na cidade de São Paulo, submetidos a uma entrevista semiestruturada. Os resultados foram analisados em quatro dimensões de análise, as quais foram desmembradas em categorias e itens. Notou-se, diante dos dados, que o perfil do Acompanhamento Terapêutico está em constante mudança e que caracterizá-lo implica a observação de variáveis aqui discutidas.
Therapeutic companions: characterization of professional practice in the perspective of Behavior Analysis
Keywords: Therapeutic companions; Behavior analysis; Clinical psychology; Acompanhante terapêutico; Análise do comportamento; Psicologia clínica